2022
DOI: 10.1155/2022/9505229
|View full text |Cite|
|
Sign up to set email alerts
|

MeQryEP: A Texture Based Descriptor for Biomedical Image Retrieval

Abstract: Image texture analysis is a dynamic area of research in computer vision and image processing, with applications ranging from medical image analysis to image segmentation to content-based image retrieval and beyond. “Quinary encoding on mesh patterns (MeQryEP)” is a new approach to extracting texture features for indexing and retrieval of biomedical images, which is implemented in this work. An extension of the previous study, this research investigates the use of local quinary patterns (LQP) on mesh patterns i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Their method outperformed other methods in four fabric datasets, with an average mAP of over 90%, but the precision dropped sharply, by 35%, when retrieving more than eight images. In 2022, Deep et al [73] introduced a texture descriptor based on the concept of LBP for conducting ImR tasks on three biomedical datasets. The results showed that their proposed method reached an Average Precision (AP) rate of 91.5%; however, the AP rate of one of the datasets was very low (46%).…”
Section: Recent Work To Retrieve Industrial and Healthcare Images Wit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their method outperformed other methods in four fabric datasets, with an average mAP of over 90%, but the precision dropped sharply, by 35%, when retrieving more than eight images. In 2022, Deep et al [73] introduced a texture descriptor based on the concept of LBP for conducting ImR tasks on three biomedical datasets. The results showed that their proposed method reached an Average Precision (AP) rate of 91.5%; however, the AP rate of one of the datasets was very low (46%).…”
Section: Recent Work To Retrieve Industrial and Healthcare Images Wit...mentioning
confidence: 99%
“…Maintaining a consistent retrieval performance using the same feature and similarity metric for different datasets is challenging in the ImR domain. Boudani et al [16] and Deep et al [73] both applied LBP-based methods for ImR tasks, but their mAPs differed across their respective datasets.…”
Section: Recent Work To Retrieve Industrial and Healthcare Images Wit...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%